Thou shalt not covet: the moderation of trait mindfulness on academic envy and ostracism - Cleoputri Yusainy; Ziadatul Hikmiah; Isma Adila; Dita Rachmayani; Natasha van Antwerpen; Deborah Turnbull (Cogent Psychology)
As future members of the academic community, the superiority that undergraduate students demonstrate by producing knowledge is often inconsistent with the prestige they obtained. The current study explored the extent to which undergraduates who experience different types of envy chose to ostracize their peers for their failings in competing, and whether this choice could be moderated by their levels of trait mindfulness. We conducted a randomized experimental design using a large number of undergraduates in Australia and Indonesia (Nfinal = 361, Mage= 21.360, SD = 1.970). Participants filled in the online scale for trait mindfulness, randomly received academic envy scenarios varied by appraisal dimensions of deservingness and control potential, then filled in manipulation check measures, a state envy scale, and an ostracism scale. As expected, we found that higher ostracism was predicted by higher malicious envy and lower benign envy (albeit less consistently). Trait mindfulness weakened the link between malicious envy and ostracism when malicious envy was high; however, the reverse effect occurred when malicious envy was low. The findings of this study underline the importance of deservingness as a key consideration for awarding academic prestige and the relevance of practicing mindfulness in higher education.